Incorporation of nanogels within calcite single crystals for the storage, protection and controlled release of active compounds. Issue 28 (28th June 2021) - Nahi, Ouassef; Kulak, Alexander N.; Kress, Thomas; Kim, Yi-Yeoun; Grendal, Ola G.; Duer, Melinda J.; Cayre, Olivier J.; Meldrum, Fiona C.
Abstract : Nanocarriers have tremendous potential for the encapsulation, storage and delivery of active compounds. Abstract : Nanocarriers have tremendous potential for the encapsulation, storage and delivery of active compounds. However, current formulations often employ open structures that achieve efficient loading of active agents, but that suffer undesired leakage and instability of the payloads over time. Here, a straightforward strategy that overcomes these issues is presented, in which protein nanogels are encapsulated within single crystals of calcite (CaCO3 ). Demonstrating our approach with bovine serum albumin (BSA) nanogels loaded with (bio)active compounds, including doxorubicin (a chemotherapeutic drug) and lysozyme (an antibacterial enzyme), we show that these nanogels can be occluded within calcite host crystals at levels of up to 45 vol%. Encapsulated within the dense mineral, the active compounds are stable against harsh conditions such as high temperature and pH, and controlled release can be triggered by a simple reduction of the pH. Comparisons with analogous systems – amorphous calcium carbonate, mesoporous vaterite (CaCO3 ) polycrystals, and calcite crystals containing polymer vesicles – demonstrate the superior encapsulation performance of the nanogel/calcite system. This opens the door to encapsulating a broad range of existing nanocarrier systems within single crystal hosts for the efficient storage, transport and controlled release of various active guest species.